Family support and motivation for recovery among patients with chronic diseases at outpatient clinics - Suraya Putri; Syarifa Atika; Dewiyuliana Dewiyuliana; Lisa Fitriani (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Chronic diseases are a global health challenge that has a significant impact on individuals and health systems. Purpose: To analyze the relationship between family support and motivation for recovery in patients with chronic diseases. Method: A descriptive analytical design with a cross-sectional approach involving 315 patients at Syiah Kuala University Teaching Hospital. Data were analyzed using the chi-square test with SPSS. Results: The results showed that patients with good family support had higher motivation to recover (40.2%) compared to those with less support (4.5%). Conversely, low motivation to recover was more often found in patients with less family support (48.2%). Statistical analysis showed a significant relationship between family support and encouragement to recover (p = 0.001). Conclusion: Family support plays an important role in increasing the motivation for recovery of patients with chronic diseases.